Optimisation of substrate angles for multi-material and multi-functional inkjet printing - Vaithilingam, Jayasheelan; Saleh, Ehab; Wildman, Ricky D.; Hague, Richard J.M.; Tuck, Christopher (Nature Publishing Group, 2018)
Three dimensional inkjet printing of multiple materials for electronics applications are challenging due to the limited material availability, inconsistencies in layer thickness between dissimilar materials and the need to expose the printed tracks of metal nanoparticles to temperature above 100 °C for sintering. It is envisaged that instead of printing a dielectric and a conductive material on the same plane, by printing conductive tracks on an angled dielectric surface, the required number of silver layers and consequently, the exposure of the polymer to high temperature and the build time of the component can be significantly reduced. Conductive tracks printed with a fixed print height (FH) showed significantly better resolution for all angles than the fixed slope (FS) sample where the print height varied to maintain the slope length. The electrical resistance of the tracks remained under 10Ω up to 60° for FH; whereas for the FS samples, the resistance remained under 10Ω for samples up to 45°. Thus by fixing the print height to 4 mm, precise tracks with low resistance can be printed at substrate angles up to 60°. By adopting this approach, the build height “Z” can be quickly attained with less exposure of the polymer to high temperature.